2000
DOI: 10.1088/0264-9381/17/14/312
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetry of topological Kerr-Newman-Taub- NUT- adS spacetimes

Abstract: We extend the topological Kerr-Newman-aDS solutions by including NUT charge and find generalizations of the Robinson-Bertotti solution to the negative cosmological constant case with different topologies. We show how all these solutions can be obtained as limits of the general Plebanski-Demianski solution.We study the supersymmetry properties of all these solutions in the context of gauged N = 2, d = 4 supergravity. Generically they preserve at most 1/4 of the total supersymmetry. In the Plebanski-Demianski ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
188
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(197 citation statements)
references
References 38 publications
8
188
0
1
Order By: Relevance
“…5 Therefore, in contrast to "flat" dilatonic RS theory, it is no longer possible to make contact with the original RS scenario [1,2]. Nor is it possible, in the limit α → 0 (φ trivial), to make contact with the solutions of [8], as can clearly seen in the conformal frame (7). The solution for Λ = 0 (Λ = 0) was given in [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…5 Therefore, in contrast to "flat" dilatonic RS theory, it is no longer possible to make contact with the original RS scenario [1,2]. Nor is it possible, in the limit α → 0 (φ trivial), to make contact with the solutions of [8], as can clearly seen in the conformal frame (7). The solution for Λ = 0 (Λ = 0) was given in [7].…”
mentioning
confidence: 99%
“…Hence, an observer living in this brane world would see both gauge as gravity physics in the same way as an observer in a four-dimensional space-time. Different generalisations of this picture including a dilaton field were given in [3]- [7] while on the other hand, generalizations to non-flat brane worlds (without dilaton) appeared in [8], where a four-dimensional cosmological constant was introduced via constant curvature branes. Here it was shown that, in the brane world scenario, the four-dimensional cosmological constant is a geometrical property of the three-brane (namely its internal curvature), which in principle can be independent of the five-dimensional one.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the remaining F1 and the NS5-brane are easy to discuss: as they couple (magnetically) to the NSNS 7-and 3-form respectively, we have that 13) and their solutions are the same as the D1 and D5-brane, up to a minus sign in the dilaton exponential (as can be expected from S-duality). We therefore find a negatively curved (AdS) F1 and a Ricci-flat NS5-brane.…”
Section: Curved Branes With Flux 41 the Scaling Solutions For Generamentioning
confidence: 78%